Implementation of Digital Financial Literacy in the Investment Decision-Making System for the Community of Padangsidimpuan City using the Analytical Hierarchy Process (AHP) Method - Nirmalahaty Harahap; Wisnu Yudhistira; Rizaldy Khair; Khairunnisa Almadany (Journal of Science and Education (JSE), 2025)
In today's digital era, digital financial literacy plays a crucial role in shaping the behavior and investment decisions of the community. Padangsidimpuan City, one of the cities in Indonesia, faces challenges in adopting and implementing digital financial literacy among its citizens. Effective and efficient investment decision-making has become vital in the current economic context, where financial information is widely available but often complex and difficult for the general public to interpret. The application of digital financial literacy can enhance individuals' abilities to manage personal finances and make wise investment decisions. However, there remains a gap in knowledge and practice in the field that hinders the optimal use of digital financial literacy. The urgency of this research lies in strengthening digital financial literacy within the community. By understanding its influence on investment decision-making, strategies can be developed to improve awareness and understanding of digital finance, thereby helping the public make more informed investment decisions. This study aims to analyze the application of digital financial literacy in the investment decision-making system in Padangsidimpuan City. The method used in this research is the Analytical Hierarchy Process (AHP), a systematic approach to solving complex decision-making problems through the ranking and evaluation of various criteria and alternatives. AHP was chosen for its unique ability to handle both subjective and objective preferences and decision-making complexities, making it highly suitable for examining the phenomenon of digital financial literacy in the context of investment decision-making.